Menemukan Islam Otentik: Menggugat Tradisi dan Modernitas - Sahidah, Ahmad (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
An emerge of various groups in society is a necessity.One of the reasons is the span of time and space from the sourceof origin belief. The issue of authenticity becomes important tolook back on to this kind of jeopardize. Review of conduct towardsthe struggle for true authenticity allows different groups to meeteach other. This possibility could happen since both of themassume the identity interdependence.